Enhancing Customer in Islamic Banking: a Case Study of Bank Syariah Indonesia’s Marketing Strategy - Hidayatullah, M.F.; Bambang Irawan; Sudaryanto; Ahmad Roziq; Ma'mun, Sukron (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The potential for sharia banking in Indonesia is very large because 87% of the Indonesian population is Muslim. However, sharia banking customers currently only reach 6.52% share of the national banking market. This qualitative research describes the marketing strategy of Bank Syariah Indonesia (BSI) in Lumajang Regency, East Java, BSI which increased customers by up to 35%, even though other sharia banks only reached approximately 12%. The results of this research are that BSI Lumajang implements the Islamic Leaders strategy, in addition to implementing the 7P marketing mix (product, price, promotion, place/distribution, people, processes, and physical evidence). The approach of Islamic figures is carried out by establishing friendship with Islamic religious figures, kiai who own pesantren, and village kiai who lead prayer congregations. By implementing a personal approach strategy with these kiai and religious figures, BSI succeeded in improving relationships so that they became BSI customers. The Islamic Leaders strategy succeeded in increasing customers by up to 35%, even though other sharia banks only achieved approximately 12